2016
DOI: 10.1007/s40122-016-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

How Resistant to Tampering are Codeine Containing Analgesics on the Market? Assessing the Potential for Opioid Extraction

Abstract: IntroductionMisuse of opioid analgesics, in combination with diversion, dependence, and fatal overdoses, presents a serious problem for public health, which affects many countries worldwide. Within this context, tampering with opioids has been associated with serious harm. The aim of the present study was to assess the tampering potential of codeine combination analgesics on the market (containing codeine/non-opioid analgesics) by the extraction of codeine.MethodsCodeine was extracted from three combination fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…We recently extracted codeine from ‘over‐the‐counter’ preparations with simple household utensils such as coffee filters and recipes that we found on the internet. Our study showed that it was possible to separate codeine from the accompanying non‐opioid analgesics, thus allowing for consumption of large codeine doses without toxic doses of ibuprofen and paracetamol . The results also indicated that codeine extraction was ineffective in some formulations, and that the amounts of active substances, codeine and non‐opioid analgesics, varied in tampering products.…”
mentioning
confidence: 73%
“…We recently extracted codeine from ‘over‐the‐counter’ preparations with simple household utensils such as coffee filters and recipes that we found on the internet. Our study showed that it was possible to separate codeine from the accompanying non‐opioid analgesics, thus allowing for consumption of large codeine doses without toxic doses of ibuprofen and paracetamol . The results also indicated that codeine extraction was ineffective in some formulations, and that the amounts of active substances, codeine and non‐opioid analgesics, varied in tampering products.…”
mentioning
confidence: 73%
“…Thus, hepatotoxicity from paracetamol, or gastrointestinal damage (haemorrhages, ulcerations, hypokalaemia, metabolic acidosis) and nephrotoxicity caused by ibuprofen are common consequences of its misuse [ 27 , 39 , 40 , 41 ]. In effort to evade these harms, various homemade extraction methods are used to separate codeine from the abovementioned drugs—for example, the so-called cold water extraction that exploits solubility differences between ingredients [ 35 , 42 , 43 ]. Lately, some pharmaceutical companies begun to incorporate physical or chemical barriers to their products as a means to combat such practices [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another alarming trend entails clandestine syntheses of more potent opioids with codeine used as a substrate. The “homebake” method results in the demethylation of codeine to morphine, while with a slightly more complex protocol [ 63 , 64 , 65 , 66 ] it is possible to obtain desomorphine—a drug with an 8–10 times stronger analgesic effect (up to 80–100 times stronger than the precursor codeine) and three times the toxicity of morphine [ 42 , 65 ]. Structural differences between these opioids are presented in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Codeine extraction has been described amongst members of drug discussion forums (Cone, 2006;Foley, Breindahl, Hindersson, Deluca, & Kimergård, 2016). One study found that extracting codeine with the use of simple techniques and household appliances can yield different amounts of codeine and non-opioid analgesics in the extracted mixtures making it difficult to control the doses (Kimergård, Deluca, Hindersson, & Breindahl, 2016b). Understanding risk factors associated with medicine tampering may help implement harm reduction interventions and deliver treatment to specific populations of polysubstance users where the risk of harm is disproportionately great (Kapitány-Fövény et al, 2015;Kimergård et al, 2016a;Talu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%